2006
DOI: 10.1021/jf0610458
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Engineering of Nicotiana tabacum for Reduced Nornicotine Content

Abstract: Alkaloid; cytochrome P450; gene silencing; nicotine N-demethylase; N'-nitrosonornicotine; plant genetic engineering; metabolic engineering; Nicotiana tabacum L.; real-time PCR; RNA interference; tobacco-specific nitrosamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 28 publications
1
50
1
Order By: Relevance
“…Our results further reinforce that hypothesis. Thus, removal of nornicotine from tobacco could be a potential strategy to reduce the levels of NNN in tobacco products (Gavilano et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Our results further reinforce that hypothesis. Thus, removal of nornicotine from tobacco could be a potential strategy to reduce the levels of NNN in tobacco products (Gavilano et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have indicated that IR constructs of transgenes can effectively induce RNA silencing to trigger knockout of specific gene expressions (Ali et al, 2010;Allen et al, 2004;Gavilano et al, 2006;Johansen and Carrington, 2001;Kusaba et al, 2003;Liu et al, 2002;Meli et al, 2010;Pandolfini et al, 2003;Segal et al, 2003;Smith et al, 2000;Xiong et al, 2005). In addition, a number of studies showed that IR constructs of transgenes containing virus-derived sequences transformed to plants can effectively protect plants from challenging viruses (Abhary et al 2006;Bucher et al 2006;Chen et al, 2004;Di Nicola-Negri et al 2005;Hammond et al 2006;Lennefors et al 2006;Pooggin et al 2003;Simón-Mateo and García, 2011;Tenllado et al 2003;Tenllado et al, 2004;Vanitharani et al, 2003;Wang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of nicotine demethylase activity is an effective mean of decreasing significantly the level of defined carcinogen present in tobacco products. Gavilano et al (2006) used RNAi for silencing the N-demethylase (CYP82E4) gene for suppressing the conversion of nicotine to nor-nicotine in tobacco (Nicotiana tabacum). Further, Lewis et al (2008) developed RNAi-silenced nicotine demethylase transgenic lines of burley tobacco line (DH98-325-5) exhibiting sixfold decrease in nor-nicotine content.…”
Section: Allergen and Toxin Eliminationmentioning
confidence: 99%